Effectiveness of Pediatric Asthma Pathways in Community Hospitals: A Multisite Quality Improvement Study. Issue 6 (November 2020) - Desai, Mansi; Caldwell, Katherine; Gupta, Nisha; Bekmezian, Arpi; Cabana, Michael D.; Auerbach, Andrew D.; Kaiser, Sunitha V.
Abstract : Introduction: Pathways guide clinicians through evidence-based care of specific conditions. Pathways have been demonstrated to improve pediatric asthma care, but mainly in studies at tertiary children's hospitals. Our global aim was to enhance the quality of asthma care across multiple measures by implementing pathways in community hospitals. Methods: This quality improvement study included children ages 2–17 years with a primary diagnosis of asthma. Data were collected before and after pathway implementation (total 28 mo). Pathway implementation involved local champions, educational meetings, audit/feedback, and electronic health record integration. Emergency department (ED) measures included severity assessment at triage, timely systemic corticosteroid administration (within 60 mins), chest radiograph (CXR) utilization, hospital admission, and length of stay (LOS). Inpatient measures included screening for secondhand tobacco and referral to cessation resources, early administration of bronchodilator via metered-dose inhaler, antibiotic prescription, LOS, and 7-day readmission/ED revisit. Analyses were done using statistical process control. Results: We analyzed 881 ED visits and 138 hospitalizations from 2 community hospitals. Pathways were associated with increases in the proportion of children with timely systemic corticosteroid administration (Site 1: 32%–57%, Site 2: 62%–75%) and screening for secondhand tobacco (Site 1: 82%–100%, Site 2: 54%–89%); and decreases in CXR utilization (Site 1: 44%–29%), ED LOS (Site 1: 230–197 mins), and antibiotic prescription (Site 2: 23%–3%). There were no significant changes in other outcomes. Conclusions: Pathways improved pediatric asthma care quality in the ED and inpatient settings of community hospitals. Abstract : Supplemental Digital Content is available in the text.